Do hypoxia and L-mimosine modulate sclerostin and dickkopf-1 production in human dental pulp-derived cells? Insights from monolayer, spheroid and tooth slice cultures - Klara Janjić; Barbara Cvikl; Christoph Kurzmann; Andreas Moritz; Hermann Agis (BMC, 2018)
Abstract Background To understand the responses of the dental pulp to hypoxia is of high relevance for regenerative endodontics and dental traumatology. Here, we aimed to reveal the effects of hypoxia and the hypoxia mimetic agent L-mimosine (L-MIM) on the production of sclerostin (SOST) and dickkopf-1 (DKK-1) in human dental pulp-derived cells (DPC). Methods DPC in monolayer, spheroid and tooth slice cultures were treated with L-MIM or hypoxia. Resazurin-based toxicity and MTT assays were performed to determine cell viability. mRNA and protein levels of SOST and DKK-1 were measured with quantitative reverse transcription PCR and ELISA, respectively. To validate the hypoxia-like response, SDF-1, VEGF and IL-8 were assessed. In addition Western blots for HIF-1α, HIF-2α and HIF-3α were done. Results Cells were vital upon treatment procedures and showed increased levels of HIF-1α, and HIF-2α. In monolayer cultures, mRNA levels of SOST and DKK-1 were downregulated by L-MIM and hypoxia, respectively. A significant downregulation of SOST by hypoxia was found at the protein level compared to untreated cells while the effect on DKK-1 and the impact of L-MIM on SOST and DKK-1 did not reach the level of significance at the protein level. In spheroid cultures, mRNA levels of SOST and DKK-1 were downregulated by L-MIM. A significant downregulation of DKK-1 upon hypoxia treatment was found at the protein level while the impact of hypoxia on SOST and the effect of L-MIM on SOST and DKK-1 did not reach the level of significance. SOST and DKK-1 were also produced in tooth slices, but no pronounced modulation by L-MIM or hypoxia was found. Evaluation of SDF-1, VEGF and IL-8 showed a hypoxia-like response in the culture models. Conclusions There is no pronounced influence of hypoxia and L-MIM on DPC viability, SOST and DKK-1 protein production. However, the specific response depends on the culture model and the level of evaluation (mRNA or protein). These results deepen our understanding about the role of hypoxia and the potential impacts of hypoxia-based strategies on dental pulp.